STATE PROTECTION OF CHILDREN FROM HARMFUL INFORMATION - Minovvarkhon Sabirovna, Yunusova (International Journal of Business, Law and Political Science, 2024)
Objective: This study examines Uzbekistan's regulatory framework for information dissemination, focusing on safeguarding societal values and protecting vulnerable populations, particularly children. Method: A qualitative approach is employed, analyzing constitutional provisions, legislative acts, government resolutions, and categorization methods for information, alongside policy assessments and comparative reviews with international practices. Results: The findings reveal a structured legal framework balancing transparency with protection. Information is categorized into five types—beneficial, neutral, harmful, culturally sensitive, and misleading—each addressed through nuanced policies. Specific measures include the 2018 law mandating age-based content classification and expert accreditation to evaluate harmful content. Challenges identified include limited parental and institutional oversight and the need for technological solutions like AI-based filters. Novelty: This research highlights the integration of age-specific digital regulations and expert accreditation as innovative tools in mitigating harmful content, presenting a model adaptable to other jurisdictions. These findings emphasize the evolving landscape of information governance and the critical need for collaborative efforts among stakeholders to ensure a safer informational ecosystem.